THE ROLE OF INTERNAL AUDIT IN ENSURING THE FINANCIAL STABILITY OF ORGANIZATIONS (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the role of internal audit systems in ensuring financial stability in enterprises and organizations, with a focus on its influence on management processes and overall effectiveness. The study explores how internal audit helps identify financial errors, weaknesses in resource management, and the efficiency of asset utilization, using both theoretical and practical approaches. Moreover, the digitization of internal audit processes and their impact on audit quality and speed are critically discussed.